#adaywithMamaJen: An Analysis of Visual Self-Representation of Motherhood on Instagram - Riyanti, Erni Dewi; Astuti, Wulan Tri (UPT Publikasi Ilmiah UNISBA, 2024)
Motherhood is culturally expected and requires women to conform to societal ideology, creating 'good mothers' ideals and media commercialization. With the growing number of social media influencers, especially on Instagram, the study aims to examine the meaning of the visual self-representation shown by the Instagram account of Jennifer Bachdim (JB) and connects to the roles of motherhood portrayed by the account. The account showcases JB's work as a mother, entrepreneur, and influencer in beauty and wellness. The study applied but was not limited to, Machin & Mayr’s multimodal critical discourse analysis and Rettberg’s self-representation theory to analyze JB’s selected reels. The results indicate that JB's selected reels represent her notion of being 'busy' as a mother of four children, entrepreneur, and influencer; yet the representation that JB builds negates the presence of helping hands in her family life. Also, JB creates a self-representation of motherhood to attract attention and followers, influencing and reshaping the media's image of successful mothers, and reinforcing intensive mothering ideology. In the selected reels, JB shapes an image closely associated with her motherhood roles. Consequently, the increasing number of followers subsequently contributes to her expanding business deals.